Electron beam induced synthesis of uranium dioxide nanoparticles: Effect of solvent composition. (September 2016) - Rath, M.C.; Keny, S.J.; Naik, D.B.
Abstract: The effect of various compositions of solvents was investigated on the electron beam induced synthesis of uranium dioxide, UO2 nanoparticles. The synthesis was carried out at different pHs from 2 to 7 in the aqueous solutions containing 10 mM uranyl nitrate and 10% 2-propanol. The formation of UO2 nanoparticles was found to occur only in the pH range from 2.5 to 3.7. Experiments were also carried out in the aqueous solutions containing various other alcohols (10% v/v) such as methanol, ethanol, 1-propanol, 1-butanol or tert -butanol as well as in solutions containing 10 mM sodium formate at pH 3.4. The formation of UO2 nanoparticles in the aqueous solutions was found to occur only in the presence of ethanol, 1-propanol, 2-propanol or 1-butanol. It is therefore confirmed that the electron beam induced synthesis of UO2 nanoparticles strongly depends on the solvent compositions as well as the pH of the medium. Graphical abstract: Highlights: UO2 nanoparticles were found to be formed in the pH range from 2.5 to 3.7. Ethanol, 1-, 2-propanol, 1-butanol support UO2 nanoparticles in aqueous solutions. Methanol, tert -butanol and formate do not favour UO2 nanoparticle formation.